REKONSTRUKSI PENEGAKAN HUKUM TERHADAP PERKARA PIDANA PEMILIHAN UMUM BERBASIS NILAI KEADILAN - Ahmad Sulchan (Jurnal Pembaharuan Hukum, 2014)
Law enforcement against criminal case elections imposed in order to address the crime of electoral violations. The level of the higher electoral violations seemed to indicate a legal loophole in the Act 8 of 2012 concerning Election, as judged not reflect the sense of justice. This research used juridical sociological issues discussed is closely related to social reality and the real behavior of the man himself. The results obtained (1) that the elections that are administrative violations under the authority of the Commission for settlement, for it contains elements of a criminal offense will be forwarded to the Police of the Republic of Indonesia for its completion, (2) Reconstruction of the settlement law enforcement criminal justice worth elections contained in Article 249 (4) regarding the limitation of time if there is no election violations, Article 249(5) of the 3-month follow-up report after being proven, Article 250 (1.d) regarding criminal acts Election forwarded to the Special Court of election, Article 250 (2) Election forwarded to the Special Court 3 (three) months, and Article 261 paragraph (1), (2), (3), and (4) of the Election Supervisory Body as investigators and prosecutors of Disputed Election which has the authorityto summons Forced, Seizure of Evidence and search of.